2001
DOI: 10.1007/s001670100225
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intratester comparison of the Rolimeter knee tester: effect of tester's experience and the examination technique

Abstract: Clinical knee examination is imperative for the prognosis, follow-up, and scientific comparison of anterior cruciate ligament surgery results. A new device, the Rolimeter knee tester was studied in this study with respect to inter- and intratester reliability. We found no significant difference in the intratester evaluation, and data were reliable between repeated measurements and between different testers with the same examination technique. The tester's experience seems to play a role using use the Rolimeter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 23 publications
6
65
2
Order By: Relevance
“…In conclusion, it can be seen from the findings of this study, and those of Muellner et al [13], that the rolimeter is a device which demonstrates both good intra-tester and inter-tester reliability in measuring anterior drawer in the knee at both 30" and 90" of flexion. It also appears that the level of experience of the rolimeter user has no significant effect on either the intra-tester or inter-tester reliability of the device.…”
Section: J Hutcher Et Al I Journal Of Orthopaedic Research 23 (2005supporting
confidence: 73%
See 3 more Smart Citations
“…In conclusion, it can be seen from the findings of this study, and those of Muellner et al [13], that the rolimeter is a device which demonstrates both good intra-tester and inter-tester reliability in measuring anterior drawer in the knee at both 30" and 90" of flexion. It also appears that the level of experience of the rolimeter user has no significant effect on either the intra-tester or inter-tester reliability of the device.…”
Section: J Hutcher Et Al I Journal Of Orthopaedic Research 23 (2005supporting
confidence: 73%
“…Previous studies on the rolimeter [2,8,13] have all used a mean of repeated recordings (usually of three attempts). This is meant to allow for some variation in the techniques used, as the rolimeter requires a manual force to cause the anterior tibial translation, and it is difficult to accurately maintain this force.…”
Section: J Hutcher Et Al I Journal Of Orthopaedic Research 23 (2005mentioning
confidence: 99%
See 2 more Smart Citations
“…Hatcher et al found interrater reliability of 0.91-0.95 by a range of skill levels [56]. Muellner found reliability of 0.71-0.90 in experienced testers, but worse in novices [57]. Papandreou found varying interrater reliability of 0.55-0.96, which they attributed to the inherent subjectivity of the testing method [58].…”
Section: Rolimetermentioning
confidence: 99%